Fibrinolytic Activity at High Altitude and Sodium Acetate Buffer - Chohan, I. S; Singh, I; Balakrihsnan, K (Thrombosis and Haemostasis, 1974)
At high altitude there is a tendency for fibrinolytic activity to be enhanced depending, perhaps, on the duration of exposure and this seems to be a protective mechanism against the development of high altitude pulmonary oedema which is associated with diminished fibrinolytic activity. The fibrinolytic response at high altitude seems to be fluctuated during the process of acclimatisation though being maintained at a plateau higher than that in the plains. It apparently results from hypoxic stress but more likely reflects the physiological response to the hypercoagulable state at high altitude. As clot lysis times in high altitude pulmonary oedema are unusually prolonged an attempt at shortening their observation in the test system is desirable. Sodium acetate, 0.12 M solution with pH 7.4 as a diluent in the low temperature technique of dilute clot lysis time is potentially effective to accelerate the lysis time by approximately 33 % compared to phosphate buffer solution of similar pH and molarity. Also the end point of disintegration of clot is more abrupt and sharply defined. Sodium acetate buffer can advantageously replace phosphate buffer as a diluent in this technique.